2021
DOI: 10.3390/biomedicines9081017
|View full text |Cite
|
Sign up to set email alerts
|

Disease-Modifying Potential of Metformin and Alendronate in an Experimental Mouse Model of Osteoarthritis

Abstract: Osteoarthritis (OA) is the most common degenerative joint disease causing progressive damages of the cartilage and subchondral bone, synovial inflammation, and severe pain. Despite the complex pathomorphological changes that occur in OA, the approach to different forms of OA is standardized. The global results from pharmacological treatment are not satisfactory. Hence, this study aimed to explore the effects of metformin, alendronate, and their combination on OA development and progression in mice with collage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…Interestingly, treatment with fenofibrate in in vitro experiments led to reduced proteoglycan loss and protected against cartilage degeneration induced by the administration of IL-1β. In our own study, a histological examination incorporating a mouse model of OA showed decreased cartilage degeneration after treatment with metformin, and the effect was more pronounced in the group treated with a combination of metformin and alendronate [ 32 ]. In patients with knee OA and accompanying obesity (BMI ≥ 30 kg/m 2 ; ≥2nd radiological grade according to Kellgren–Lawrence scale), metformin administration has been associated with slower cartilage volume loss in the medial compartment of the joint assessed via MRI after 4 years.…”
Section: Therapeutic Considerations In Metabolic Knee Osteoarthritismentioning
confidence: 99%
“…Interestingly, treatment with fenofibrate in in vitro experiments led to reduced proteoglycan loss and protected against cartilage degeneration induced by the administration of IL-1β. In our own study, a histological examination incorporating a mouse model of OA showed decreased cartilage degeneration after treatment with metformin, and the effect was more pronounced in the group treated with a combination of metformin and alendronate [ 32 ]. In patients with knee OA and accompanying obesity (BMI ≥ 30 kg/m 2 ; ≥2nd radiological grade according to Kellgren–Lawrence scale), metformin administration has been associated with slower cartilage volume loss in the medial compartment of the joint assessed via MRI after 4 years.…”
Section: Therapeutic Considerations In Metabolic Knee Osteoarthritismentioning
confidence: 99%
“… 101 , 102 Treatment with metformin increased antinociceptive activity, and anti-inflammatory and chondroprotective effects in OA mice with monosodium iodoacetate (MIA) model 103 as well as with collagenase-induced osteoarthritis (CIOA) model. 104 , 105 …”
Section: Repurposed Drugs Already In Phase II and Iii Trials Either A...mentioning
confidence: 99%
“…101,102 Treatment with metformin increased antinociceptive activity, and anti-inflammatory and chondroprotective effects in OA mice with monosodium iodoacetate (MIA) model 103 as well as with collagenaseinduced osteoarthritis (CIOA) model. 104,105 A combination of metformin with COX-2 inhibitors (n = 968) reduced the risk of joint replacement surgery (12.81% versus 16.22%) over 10 years compared with COX-2 inhibitors alone (n = 1936) in type 2 DM patients with OA in a nationwide, retrospective, matched-cohort study. 106 However, data on the OA severity, disease duration and other assessment scores are unavailable, limiting the validity of study findings.…”
Section: Agents With Other Mechanisms Biguanides (Metformin)mentioning
confidence: 99%
“…Similar to this study, another study demonstrated that intraarticular injections of metformin in DMM-induced OA mice mitigated cartilage degradation by activating AMPK/the specifically silent information regulator 1 (SIRT1)-mediated autophagy [ 15 ]. Besides, the cartilage protective effect of metformin was also confirmed in both collagenase-induced and papain-induced OA mouse models [ 16 , 17 ]. Three other in vivo studies demonstrated that metformin also had an analgesic effect along with the joint structure-protective effects.…”
Section: Introductionmentioning
confidence: 99%